Розвиток інформаційної компетентності фахівців в освітньому середовищі - Чичук Антоніна; Chychuk Antonina; Csicsuk Antonina; Гончарук Віталій; Goncharuk Vitaliy; Кваснюк Владислав; Vladyslav Kvasniuk (Видавництво «Код», 2024)
Резюме. У статті описано розвиток інформаційної компетентності фахівців в освітньому середовищі. Висвітлено інформаційно-педагогічну компетентність фахівця вищої школи. Описано стратегічні цілі системи освіти. Означено завдання для успішного використання інформаційно-комунікаційних технологій у системі підготовки фахівців ЗВО. Розкрито тенденції вдосконалення інформаційної підготовки студентів, що ґрунтується на покращенні не тільки організації та змісту, а й на використанні у навчальному процесі сучасних засобів навчання. Наголошено, що зміни у сфері національної освіти, що вводяться у високі освітні технології висувають нові вимоги до рівня професіоналізму сучасного фахівця ЗВО.

Abstract. The article describes the development of information competence of specialists in the educational environment. The informational and pedagogical competence of a higher school specialist is highlighted. The strategic goals of the education system are described. The tasks for the successful use of information and communication technologies in the system of training of specialists in higher education are defined. The trends of improving the information training of students, which is based on improving not only the organization and content, but also the use of modern teaching aids in the educational process, are revealed. It is emphasized that the changes in the field of national education, which are introduced in high educational technologies, put forward new requirements for the level of professionalism of a modern specialist in higher education. The information society of the 21st century is characterized by the use of information technologies in the professional activities of specialists. Problems related to the informational training of students, especially psychological and pedagogical and other humanitarian specialties, are ambiguous and multifaceted. In the conditions of the informatization of the higher education system, information training is a mandatory component of the educational process, aimed at training future specialists in the field of ICT use in order to carry out information activities and information interaction both between the participants of the educational process and between users and an interactive learning tool that functions based on ICT. Information competence as a basic competence implies the availability of the future specialist, possibilities and limitations of technical means and information and communication technologies. The information and pedagogical competence of a higher school teacher is a component of his professional and pedagogical culture, the most important indicator of his professional skill and compliance with world standards in the field of higher education. The problem of the formation of the information society and its component problem of informatization of education should be considered in close connection with the problem of the future sustainable development of civilization. The formation of the so-called information and pedagogical competence of the teacher of higher education, whose main professional function today is the implementation of new information technologies in education.
Development of the information competence of specialists in the educational environment
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00014093
https://akim.uz.ua/img/%D0%A7%D0%B5%D1%80%D0%BA%D0%B0%D1%81%D0%BE%D0%B2/%D0%9D%D0%97/6/6_8.pdf
Keywords: інформаційна компетентність; система освіти; фахівці; навчальний процес; національна освіта; технології